KONSEP ECOLOGICAL CITY DALAM KERANGKA KONSEP EKOLOGI KOTA DAN KOTA BERKELANJUTAN - Enni Lindia Mayona (Universitas Islam Sultan Agung Semarang, 2021)
ABSTRACTCity growth that continues to occur is unavoidable and affects the environment, so an ecological approach is needed to overcome it. One of the city concepts that has developed along with the historical perspective of urban ecology is the ecological city (ecocity). In the development of ecocity in several countries that carry the theme of sustainability city, both practice and concept do not explain the